Patent ductus arteriosus ligation on neurodevelopmental outcomes at corrected 2 years - YoungAh Youn; Yu-mi Seo; Sook-Kyung Yum; In Kyung Sung (BMC, 2019)
Abstract Background Our aim in this study was to evaluate whether very low birth weight infants (VLBWI) ligated for patent ductus arteriosus (PDA) were associated with worse neurodevelopmental outcomes at corrected 2 years. The ligated group was subdivided into ≤2 weeks of life (early) and ligated > 2 weeks of life (late) groups and compared the in-hospital morbidities and long term outcomes. Methods Between Dec 2013 and Dec 2015, VLBWI diagnosed with hs PDA were evaluated. Results Of the 191 VLBW infants with hs PDA, 28 (14.7%) infants had surgical ligation for PDA; 11 (39%) infants had EL and 17 (61%) infants had LL. Surgical ligation of hs PDA group had higher morbidities and mortality. Among the142 (83.0%) infants of 171 VLBWI with PDA survived, infants who were ligated had significantly lower scores of Bayley Scales of Infant and Toddler Development III at corrected age of 18 months. However, among the ligated group, there was little evidence of differences between the EL and LL groups. In a multivariable logistic regression analysis, only longer exposure of hs PDA and mechanical ventilation were consistently associated with worse neurodevelopmental outcomes. Conclusion Our results suggest that surgical ligation for hs PDA may not increase risk for poor neurodevelopmental outcomes at corrected 2 years of age. The early surgical ligation may not be a risk factor.